Against Exclusive Survivalism: Preventing Lost Life and Protecting the Disadvantaged in Resource Allocation. Issue 5 (16th September 2021) - Persad, Govind
Abstract: When life‐saving medical resources are scarce and not everyone can be saved, is the only relevant goal saving the most lives? Or can other factors be considered, at least as tiebreakers, such as how early in life the people we don't save will die or how much future life they are likely to lose? This commentary defends a multiprinciple allocation approach that considers objectives in addition to saving more lives, including preventing early death and preventing harm in the form of lost future life. Particularly compared to an arbitrary, coin‐flip tiebreaker, this multiprinciple approach more effectively prevents harm, prioritizes the worst‐off, mitigates socioeconomic and racial health disparities, and tracks public values regarding allocation under scarcity—and is legally sound .